Influence of Mild Dehydration on Exercise Performance - Aragón Vargas, Luis Fernando (2001)
This presentation summarizes some initial evidence for an impairment of exercise performance due to mild dehydration. An attempt is made at defining mild dehydration, and preliminary hypotheses are presented.